The Never-End Studentship of Women Teachers: Character Designs Under the Influence of Masculine Subject in the Novels The Wren, Vurun Kahpeye, and Ankara - Berna Terzi Eskin (Türk dili ve edebiyatı dergisi, 2024)
The Wren (1921), which was published before the proclamation of the Republic of Türkiye, as well as Vurun Kahpeye (1923) and Ankara (1933), which were published in the following period, are highly representative works that provide data on the sociology of their periods. The respective authors of these novels, Reşat Nuri Güntekin, Halide Edip Adıvar and Yakup Kadri Karaosmanoğlu, were also prominent figures in the Turkish literature of the Republican era, as well as influential figures who were involved in Turkish political history with their various discourses and activities. This article will utilize the opportunities provided by the feminist literary criticism to comparatively analyze the character designs of the female teacher characters in these three novels that were written at a time dominated by nationalist and idealist discourses. The article will discuss these teachers’ motivations for pursuing their ideals, their reasons for devoting themselves to patriotic service, and their experiences on this path in the context of the hypothesis that the authors had assigned male protagonists around the female teachers to be their teachers. Feride, Aliye, and Selma, the protagonists of the novels in question, seem to have been initially conceived as teachers with similar ideals and who meet on the fundamental point of serving the homeland. When considering this basic commonality, the article will discuss whether any fictional difference occurs in the novels of male and female authors in the context of the design of the female teacher and her relations in social life, in which the concept of gender is positioned alongside the ideal of patriotic service in the case of female teachers. The study will also discuss the influence of the masculine subject in fiction.